In vino veritas. An assessment of current research of amphorae contents from Conimbriga (Portugal) - Buraca, Ida; Oliveira, César; Elezi, Gazmend; Connan, Jacques; Morais, Rui; Correia, Virgílio (Imprensa da Universidade de Coimbra, 2025)
This paper proposes an evaluation of current projects for identifying the contents of assumed wine transport amphorae recovered in the archaeological excavations in Conimbriga (prov. Lusitania, Portugal). The sampling strategy of known typologies of wine amphorae of Italic, Gaullish and Iberian origin, as well as other, locally produced typologies of uncertain use is described, as well as the methodologies of analysis, both by GC-MS and by LC-MS/MS. The results of those analyses are presented in conjunction with the typological classification, as means to assess the weight of the production of wine destined to export in the context of the local agricultural activity. Methodological issues concerning sample retrieval and analytical procedures are discussed in the context of planned future research.
Keywords: Amphorae; Wine; Roman economy; Gas Chromatography; Liquid Chromatography